DISCOURSE GENDER IN PERSPECTIVE OF HUMAN RIGHTS: A TURNING POINT PROTECTION LAWS TOWARD FEMALE WORKERS - Annisa Cahaya Pratiwi; Teta Anisah AR; Reza Torio Kamba (Universitas Muhammadiyah Metro, 2017)
Indonesia as legal state ensure protection of human rights for each citizen. Recognition human rights in indonesia can not be separated from insurance against equal rights to have jobs between the man and woman. The one of gender discrimination can be felt in the workplace. Protection toward female workers is to ensure of fundamental rights workers / labor of women and ensure an equal opportunity and treatment without discrimination to realize prosperous female workers and their household by keep considering the development the business world. Every worker women is having a fundamental rights as regulated by law. In a juridical manner the constitution of 1945 provide legal protection toward any person to obtain work and the decent life for humanity. The form of an acknowledgement of women’s rights internationally also had been recognised by the passing CEDAW (Convention on the Elimination of All Forms of Discrimination Againts Women). It means, there is no again discrimination against women’s rights to work and develop itself. Basically female workers are having huge enough contribution toward the implementation of the national development. For it, protection laws toward labor woman very important for guaranteeing a decent welfare for female workers and his family without any discrimination gender. The purpose of this research is to assess legal protection that has been given by the government on the welfare of female workers.